Temporal Trends in Deep Surgical Site Infections After Six Orthopaedic Procedures Over a 12-year Period Within a US-based Healthcare System. Issue 21 (1st November 2022) - Prentice, Heather A.; Chan, Priscilla H.; Champsi, Jamila H.; Clutter, Dana S.; Maletis, Gregory B.; Mohan, Vivek; Namba, Robert S.; Reddy, Nithin C.; Hinman, Adrian D.; Fang, Andrew S.; Yian, Edward; Navarro, Ronald A.; et al.
Abstract : Introduction: Centers of excellence and bundled payment models have driven perioperative optimization and surgical site infection (SSI) prevention with decolonization protocols and antibiotic prophylaxis strategies. We sought to evaluate time trends in the incidence of deep SSI and its causative organisms after six orthopaedic procedures in a US-based integrated healthcare system. Methods: We conducted a population-level time-trend study using data from Kaiser Permanente's orthopaedic registries. All patients who underwent primary anterior cruciate ligament reconstruction (ACLR), total knee arthroplasty (TKA), elective total hip arthroplasty (THA), hip fracture repair, shoulder arthroplasty, and spine surgery were identified (2009 to 2020). The annual incidence of 90-day deep SSI was identified according to the National Healthcare Safety Network/Centers for Disease Control and Prevention guidelines with manual chart validation for identified infections. Poisson regression was used to evaluate annual trends in SSI incidence with surgical year as the exposure of interest. Annual trends in overall incidence and organism-specific incidence were considered. Results: The final study sample was composed of 465, 797 primary orthopaedic procedures. Over the 12-year study period, a decreasing trend in deep SSI was observed for ACLR and hip fracture repair. Although there was variation in incidence rates for specific operative years for TKA, elective THA, shoulder arthroplasty, and spine surgery, no consistent decreasing trends over time were found. Decreasing rates of Staphylococcus aureus infections over time after hip fracture repair, shoulder arthroplasty, and spine surgery and decreasing trends in antibiotic resistance after elective THA and spine surgery were also observed. Increasing trends of polymicrobial infections were observed after TKA and Cutibacterium acnes after elective THA. Conclusions: The overall incidence of deep SSI after six orthopaedic procedures was rare. Decreasing SSI rates were observed for ACLR and hip fracture repair within our US-based healthcare system. Polymicrobial infections after TKA and Cutibacterium acnes after elective THA warrant closer surveillance. Level of Evidence: IV